Influence of equity sensitivity on cooperation intention: Moderation effect of cooperation/competition and exploring psychological process - Park, Seung Rib; Suh, Young Won (Korean Journal of Industrial and Organizational Psychology, 2018)
An experimental study was conducted to find a possible answer for the inconsistent results of the relationship between the equity sensitivity and organizational citizenship behavior(OCB) in previous studies. Because OCB could be observed only in organizational context, cooperation intention, as a dependent variable, was used for the experiment. The data of 89 students, obtained by the experiment, were used for the analysis. The results showed that benevolents, who were highly cooperative, decreased the cooperation intention when others competed. In addition, even though we did not develop specific hypotheses, by using an survey gauging competition orientation, choice autonomy, egocentrism, fairness perception, rationality and justification on cooperation/competition of other, the differences between benevolents and entitileds, in terms of their attitudes and perception, were investigated. Based on the results, the psychological process of changing cooperation intention and future research were discussed.